Alasan India Bergabung dengan Shanghai Cooperation Organization - Arifin, Bahrul Ulum (University of Jember, 2021)
India joined SCO in 2006 as an observer country and officially became a SCO member country in 2017 Relations between China and India have not been able to accept each other so far because the two countries have quite a poor diplomatic history. This raises the question of why India decided to join the SCO amid poor diplomatic relations with China as the inisiator of the organization. To analyze these problems, the CBM concept and neoliberal institutionalism theory will be used to find out why India joined the SCO. This study us a qualitative descriptive method using secondary data. The process of collecting data needed using library research techniques. The data used in this study is information of SCO and how India use SCO as their instrument amid their relationships with China to build CBM and to pursue benefits from joining SCO